Intertextual Illuminations: “The Lighthouse Keeper of Aspinwall” by Henryk Sienkiewicz in Malcolm Lowry’s “Through the Panama” - Dorota Filipczak (Text Matters, 2016)
The article offers a reading of “Through the Panama” by Malcom Lowry in light of an intertext connected with Polish literature. Lowry mentions a short story “The Lighthouse Keeper of Aspinwall” by the Polish writer Henryk Sienkiewicz, the Nobel prize winner for the whole of his literary output. What Lowry stresses in his intertextual allusion is the perilous illumination that the eponymous lighthouse keeper experiences. The article contends that the condition of the lighthouse keeper anticipates that of the Lowry protagonist who in “Through the Panama” fears death by his own book, or, to take Lowry’s other phrase, being “Joyced in his own petard.” Basing her analysis on Mieke Bal’s idea of a participatory exhibition where the viewer decides how to approach a video installation, and can do so by engaging with a single detail, Filipczak treats Lowry’s text as a multimodal work where such a detail may give rise to a reassessment of the reading experience. Since the allusion to the Polish text has only elicited fragmentary responses among the Lowry critics, Filipczak decides to fill in the gap by providing her interpretation of the lighthouse keeper’s perilous illumination mentioned by Lowry in the margins of his work, and by analyzing it in the context of major Romantic texts, notably the epic poem Master Thaddeus by Adam Mickiewicz whose words trigger the lighthouse keeper’s experience, and The Rime of the Ancient Mariner by Samuel Taylor Coleridge, whose text is quoted in the margins of “Through the Panama.” This choice allows to throw a different light on Lowry’s work which is also inhabited by echoes of futurist attitude to the machine and the Kafkaesque fear of being locked in one of the many locks of the canal “as if in experience.”